ANALISIS PEMASARAN CABAI MERAH DENGAN PENDEKATAN STRUCTURE CONDUCT AND PERFORMANCE DI LANGKAT - Sibuea, Mhd Buhari; Sulastri, Sulastri; Sibuea, Faiz Ahmad; Martial, Tri; Fitriani, Fitriani; Mukhlis, Mukhlis (Program Studi Agribisnis Fakultas Pertanian, 2025)
This study aims to (1) identify the marketing channel of curly red chili in Se Bingai District, Langkat Regency, and (2) analyze its marketing efficiency based on the market structure approach, market conduct, and market performance or SCP approach in the region. The research was conducted in Se Bingai District, Langkat Regency, from September to October 2024. Data were analyzed using descriptive qualitative and quantitative methods with the SCP approach (structure, conduct, and performance). The results showed that there were four marketing channels in Sei Bingai District, Langkat Regency. Market concentration is 74%, which indicates market dominance by several large actors. In addition, the Minimum Efficient Scale (MES) value in red chili marketing in Sei Bingai District was recorded at 26%, indicating inefficiency in the scale of production and distribution. The study also found that farmer's share in the red chili marketing channel varied, with values of 59%, 61%, 64%, and 77% reflecting the imbalance of profits received by farmers along the marketing chain, resulting in low profit margins. This condition indicates distribution inefficiencies that need to be corrected. The market performance shows an uneven distribution of margins, farmers share, and profit and cost ratios in each marketing institution. Based on the analysis, marketing channel four was identified as the most efficient option and worthy of consideration by farmers. To improve farmers' welfare, the government can implement strategic measures to address various issues, such as price fluctuations, market dominance by certain parties, and uneven distribution. These include more intensive price monitoring, stabilizing the supply and price of red chili, empowering farmers through strengthening cooperatives and access to market information, and improving transportation infrastructure to reduce the cost of red chili distribution.